Mental Fatigue among University Teachers (Journal Of Educational and Psychological Researches, 2023)
The current research aims to measure the level of mental fatigue among the teachers of the University of Baghdad, as well as to measure the significant differences according to the variable of mental fatigue in terms of male and female teachers, specialization (humanitarian, scientific), and title (professor, assistant professor, lecturer). To achieve these current goals, a random sample of (300) teachers from University of Baghdad was selected for the academic year 2019-2020. To measure the mental fatigue, the researcher developed a tool to measure the variable included (56) items. The research revealed that the study sample is mentally tired, the female sample is more mentally tired than males, there are no statistically significant differences according to the variable of specializations (humanitarian and scientific), while there are significant differences with respect to the scientific title and in favor of the title of professor, as the title of professor is more mentally tired than the titles of assistant professor and teacher and that the title of assistant professor More tired of my mind than the title of teacher. As for the interaction between gender, specialization and scientific title, there is no statistically significant. According to the results reached by the researcher, she presented a number of conclusions, recommendations and suggestions mentioned in the fourth chapter.